'It's not just the economy, stupid'. The multi-directional security effects of the private sector in post-conflict reconstruction. Issue 4 (4th July 2017) - Martin, Mary; Bojicic-Dzelilovic, Vesna
Abstract: Using a human security lens, this article explores the interface between transnational corporations (TNCs) and post-conflict, post-crisis societies. It demonstrates how TNCs influence political and economic transition, through impacting the everyday experience of security, creating multiple and ambiguous effects on individuals and communities. Examples of two foreign corporate engagements: carmaker Fiat's investment in Serbia and steelmaker ArcelorMittal's takeover in Zenica in Bosnia-Herzegovina are used to illustrate the density of relationships between global companies, host governments, civil society and local communities whose effects extend beyond economics to broader aspects of the conflict space, and have a bearing on the transition and reconstruction agenda. Our findings question the quality of development and industrialisation policies championed by post-conflict reconstruction approaches, and challenge the assumption that economic growth and investment, by foreign companies in particular, will necessarily deliver peaceful transition. The article contributes to the scholarly debate about the connection between security and development, and to policy discussions about appropriate means for reviving economies within externally led peace-building and conflict prevention initiatives.